User experience and digital government: exploring a practice-based participatory approach to identify research opportunities - Sperano, Isabelle; Andruchow, Robert; Petryshyn, Luca; Chu, Vik (My University, 2022)
In this case study, the research team (RT) explores user experience design in relation to digital practices adopted by governments. The goal of this first phase was to identify research opportunities. To do so, the RT adopted a practice-centered participatory research approach (Holkup, 2004). The RT began a partnership with a municipal government (City of Edmonton). Regular meetings were held with the partner organization to discuss—among other things—the organization’s structure, current and future projects, the digital editorial strategies implemented by the organization, and the organization's issues and constraints when designing digital services. This allowed the teams to identify not only interesting research questions but also potential teaching collaborations related to work-integrated learning. In this paper, the practice-based participatory research approach is explained, the timeline and the outcome of the partnership are presented, and the lessons learned through that process are shared.
Keywords: user experience design; practice-led research; design education; digital transformation; human-centered design